A new species of Calappa Weber, 1795 (Crustacea: Decapoda: Calappidae) from East and South Africa - Lai, Joelle C.y.; Ng, Peter K.l. (Zootaxa, 2006)
A new species of box crab, Calappa africana, new species (Brachyura: Calappidae) is described from East and South Africa. The species, previously misidentified as C. japonica Ortmann, 1892, differs from C. japonica by its live colouration, carapace shape, and the morphologies of the manus and merus of the cheliped and male first gonopod. In addition, a new lectotype for C. exanthematosa, a junior synonym of C. japonica, is selected.